2018
DOI: 10.1051/matecconf/201815601010
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase Enzyme Production From Rice Straw Using Solid State Fermentation and Fungi Aspergillus niger ITBCC L74

Abstract: Rice straw is one of very abundant waste of agricultural and has not utilized maximally. This waste contain cellulose and potential in the manufacture of cellulase enzymes. Research on the production of cellulase enzyme from lignocellulose has been done a lot of enzyme activity is still low. This research using cellulose is 71.95% and conducted with 6 stages. First, the preparation of raw material. Second, the decrease of lignin content with alkali pretreatment. Third, the breeding of fungi Aspergillus niger I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(22 reference statements)
1
3
0
2
Order By: Relevance
“…The peak enzyme activity (121.036 U/mL) was recorded (Figure 2A) specifically on day 4 of fermentation. This situation suggested a feasible harvest (enzyme) at about 96 h (on day 4) of fermentation, similar to the findings published elsewhere (Abubakar and Oloyede, 2013;Costa et al, 2021;Maftukhah and Abdullah, 2018;Okoye et al, 2013). The incubation period, however, would depend on a number of factors, such as the availability/level of nutrients, fermentation environment, nature of fermenting organisms and the physiological conditions influencing the (fermentation) process (Patil and Dayanand, 2006;Shivasharanappa et al, 2014).…”
Section: Enzyme Production Ammonium Sulfate Precipitation Profile And...supporting
confidence: 89%
“…The peak enzyme activity (121.036 U/mL) was recorded (Figure 2A) specifically on day 4 of fermentation. This situation suggested a feasible harvest (enzyme) at about 96 h (on day 4) of fermentation, similar to the findings published elsewhere (Abubakar and Oloyede, 2013;Costa et al, 2021;Maftukhah and Abdullah, 2018;Okoye et al, 2013). The incubation period, however, would depend on a number of factors, such as the availability/level of nutrients, fermentation environment, nature of fermenting organisms and the physiological conditions influencing the (fermentation) process (Patil and Dayanand, 2006;Shivasharanappa et al, 2014).…”
Section: Enzyme Production Ammonium Sulfate Precipitation Profile And...supporting
confidence: 89%
“…The enzyme assay was carried out on each T. reesei and A. awamori sample for the three incubation times at 3, 5, and 7 days post-incorporation (DPI) using the method of Maftukhah and Abdullah [ 16 ]. In brief, a rolled Whatman no.1 filter paper strip, of the dimensions 1.0 × 6 cm (50 mg), was placed into each assay tube.…”
Section: Methodsmentioning
confidence: 99%
“…Evelyn [21] reported that Eupenicillium javanicum can produce cellulase using pineapple crown leaves waste with the highest activity after 4 days of incubation at 35 °C through solid-state fermentation. Maftukhah and Abdullah [22] also reported that A. niger can produce cellulase from rice straw under the SSF method with the optimum incubation time being 6 days at 30 °C. Trichoderma viride can produce cellulase using maize husk silage with the highest activity after 7 days of incubation at 30 °C through the SSF method [23].…”
Section: Cellulase Productionmentioning
confidence: 99%